Efforts to Improve the Learning Outcomeso Class XI Students' Smashes through Plyometric Training - Nurdiansyah, Dani; Firmana, Iif; Rahman, Ramdhani; Agustan, Boby (JOURNAL RESPECS (Research Physical Education and Sports), 2024)
This study aims to determine the effect of Plyometric Exercise on the smash learning outcomes of class XI students of SMK NEGERI 1 Ciamis. This research method is a quantitative method with experiments, using a pre-test-post-test group research design. The population in this study was male students of class XI SMK NEGERI 1 Ciamis 30, the sampling technique applied in this study was purposive sampling. The instrument used in the smash test research. The results of the statistical hypothesis t test. From the calculation of the two pre-test and post-test data, the t-count is 3.89 and with n17 and a significance level of 0.05, from the list of tables attached, the t-table is 2.11. If compared, it can be seen that the value of t count (3.89 > 2.11) t table, then HO is rejected. With the rejection of HO, it is concluded that there is an effect of Plyometric Exercise on the smash learning outcomes of class XI students of SMK NEGERI 1 Ciamis.